TRANSCUTANEOUS MULTICHANNEL ELECTROGASTROGRAPHY: NORMAL PARAMETERS IN A BRAZILIAN POPULATION - CARVALHO,Nayara Salgado (2020)
ABSTRACT BACKGROUND: Electrogastrography (EGG) is a noninvasive technique for the assessment of gastric myoelectrical activity using electrodes placed on the abdominal surface. Changes in gastric myoelectrical activity may be associated with diseases such as gastroparesis, functional dyspepsia, nausea, and recurrent vomiting. In Brazil, no studies to date have assessed gastric myoelectrical activity using multichannel EGG in healthy individuals. OBJECTIVE: To establish normal values of transcutaneous multichannel EGG in healthy Brazilian individuals. METHODS: This was a prospective study including 20 healthy individuals who underwent EGG. Recording was performed during two periods: a preprandial recording was performed for 30 minutes, and a postprandial recording was performed for 30 minutes after a soft-solid meal of 400 kcal (20 grams of proteins, 60 grams of carbohydrates, and 9 grams of fat). RESULTS: We assessed dominant frequency (DF) parameters, %DF distribution, the instability coefficient, and the power ratio (PR). A total of 20 individuals (11 women and 9 men) with a mean age of 39.5±7.4 years were included. Mean DF (95%CI) ranged from 2.4 to 3.1 cpm in the resting phase and 2.6 to 3.2 cpm in the postprandial period. The %DF in normogastria range was >70% in all healthy individuals. We identified that only one individual did not present a positive response to the test meal, and the other 19 individuals showed a PR greater than 1. The instability coefficient did not change significantly with meal intake. CONCLUSION: Multichannel EGG may be applied in future studies to evaluate gastric motility disorders in the Brazilian population.